GARBHASANSKARA: A MIRACLE TO WOMAN (AYUSHDHARA, 2021)
Garbhasanskara means reforming, polishing and ultimate moulding and cultivating the unborn. Simply, we can say, it is a process of selecting and transmitting positive influence by means of Yoga, reading, thinking, praying including healthy eating and cheerful behaviour. There is special bond between mother and baby due to Garbha sanskara. It is a process of training the baby as well as mothers mind during pregnancy. Pre-planning for pregnancy (Supraja janan), preparing the body in advance before conceiving helps greatly in having a healthy progeny. Sanskara is Sanskaro hi Gunaantaradhanam means to substitute bad traits by superior ones. In this review, a complete description about the Garbhasanskara has been discussed, along with these essential factors for conception, Sodhana (purificatory process), Rasayan and Vajikarana, Ahara vihara, Garbhini paricharya, Mantra, meditation, stress and Pranayama.